2021
DOI: 10.1038/s41598-021-84991-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high proportion concentrate dietary on Yak jejunal structure, physiological function and protein composition during cold season

Abstract: The current study aimed to investigate the damage of long-term high concentrate diet feeding pattern on Yak jejunal structure, physiological function and protein composition during cold season. Twelve Datong male Yak (Bos grunniens) with the same age from cold season were randomly selected and slaughtered to determine Yak jejunal digestive enzyme activity, morphology and protein composition on different feeding patterns in Tibetan Plateau. The results showed that Yak jejunum digestive enzyme activity and morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The digestive enzymes’ activity is known to affect the activity of ruminal microbes; improve the digestion, absorption, and metabolism of nutrients; and maintain the rumen’s function and health. Studies have confirmed that when feed management is not correct, a high-concentrate fattening diet can reduce the activities of digestive enzymes such as lipase, trypsin, and amylase in ruminants and cause ruminal acidosis [ 20 , 21 ]. In our study, in the CON treatment group, the long-term high-concentration concentrate feeding mode will weaken the activities of pepsin and cellulase, which may be caused by the inactivation of digestive enzymes in Hu sheep caused by high-concentration feed.…”
Section: Discussionmentioning
confidence: 99%
“…The digestive enzymes’ activity is known to affect the activity of ruminal microbes; improve the digestion, absorption, and metabolism of nutrients; and maintain the rumen’s function and health. Studies have confirmed that when feed management is not correct, a high-concentrate fattening diet can reduce the activities of digestive enzymes such as lipase, trypsin, and amylase in ruminants and cause ruminal acidosis [ 20 , 21 ]. In our study, in the CON treatment group, the long-term high-concentration concentrate feeding mode will weaken the activities of pepsin and cellulase, which may be caused by the inactivation of digestive enzymes in Hu sheep caused by high-concentration feed.…”
Section: Discussionmentioning
confidence: 99%